2016
DOI: 10.1016/j.bpj.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Bilayer Dynamics Probed by a Carbon Dot-Phospholipid Conjugate

Abstract: Elucidating the dynamic properties of membranes is important for understanding fundamental cellular processes and for shedding light on the interactions of proteins, drugs, and viruses with the cell surface. Dynamic studies of lipid bilayers have been constrained, however, by the relatively small number of pertinent molecular probes and the limited physicochemical properties of the probes. We show that a lipid conjugate comprised of a fluorescent carbon dot (C-dot) covalently attached to a phospholipid constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 62 publications
(67 reference statements)
1
35
0
Order By: Relevance
“…The fluorescence properties of C‐dots are known to exhibit sensitivity to the molecular environments of the particles . In particular, shifts in the emission peaks have been reported following covalent coupling of C‐dots to other substances . Indeed, the experimentally significant shift of the emission peak depicted in Figure D, from around 450 nm in the case of soluble C‐dots prepared from the gemini glucose‐derivative surfactant to approximately 430 nm for the WS 2 ‐C‐dot system, is indicative of covalent conjugation of the C‐dots and WS 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The fluorescence properties of C‐dots are known to exhibit sensitivity to the molecular environments of the particles . In particular, shifts in the emission peaks have been reported following covalent coupling of C‐dots to other substances . Indeed, the experimentally significant shift of the emission peak depicted in Figure D, from around 450 nm in the case of soluble C‐dots prepared from the gemini glucose‐derivative surfactant to approximately 430 nm for the WS 2 ‐C‐dot system, is indicative of covalent conjugation of the C‐dots and WS 2 nanoparticles.…”
Section: Resultsmentioning
confidence: 94%
“…[16,18] In particular, shifts in the emission peaks have been reported following covalent coupling of C-dotst oo ther substances. [18,19] Indeed, the experimentally significant shift of the emission peak depicted in Figure 2D,f rom around4 50 nm in the case of soluble Cdots preparedf rom the geminig lucose-derivative surfactantt o approximately 430 nm for the WS 2 -C-dot system, is indicative of covalent conjugation of the C-dots and WS 2 nanoparticles. Examination of other excitation-dependent emission peaks revealed similar shifts between soluble C-dots and WS 2 -attached C-dots ( Figure S4, SI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…199 Jelinek and colleagues made signicant contributions to elucidate the interaction of CQDs with lipids/ membranes. [200][201][202] In one study, they showed that amphiphilic CQDs could insert into the lipid bilayer of giant vesicles and induce FRET energy transfer from the CQDs to dyes embedded in the membrane. 203 By conjugating the amphiphilic CQDs with phospholipids, the same group developed a new probe for the study of the environment and processes occurring in membranes.…”
Section: Interactions In Functionalized O-dotsmentioning
confidence: 99%
“…Since then, the simplicity of synthesis and unique properties of CQDs has attracted lots of interest which are reflected in publications relating their synthetic methodologies optical properties and various applications [2][3][4][5][6][7][8][9][10]. Carbon quantum dots (CQDs) have inspired extensive studies on them due to their great potential in the biological field and ability to interact with surfactants [11] model lipid bilayers [12], and biomembranes [13].…”
Section: Introductionmentioning
confidence: 99%